The Iraqi Student-Teachers’ Pronunciation between the Restricted RP and the Widespread GA - Haifa Adnan Salman Al-Kan’aan (PROSPECTIVE RESEARCHES, 2023)
One of the difficulties encountered by the student teachers of the teachingtraining institute/ Nineveh is the learners’ inability to put into practice much of their theoretical knowledge as regards the model of pronunciation used (as a standard) in TEFL, i.e. RP. This is so because of the sound system operating in the learners’ mother tongue (MT) on the one hand, and their frequent exposure to another predominant English accent, i.e. GA through the mass media, on the other. This study aims at verifying the validity of these considerations. It consists of a two-fold experimental design: the first is a word-pronunciation test conducted to test the proposed hypothesis; the second is a three-item questionnaire constructed to further verify the applicability of the hypothesis. The database for this study consists of recorded samples from 13 student teachers of the fifth year/ Department of English/ Teacher Training Institute- Nineveh of the academic year 2009- 2010. The results of the study suggest that the student teachers show an approximation to GA in much of their performance though GA is not used as a standard of pronunciation in the TEFL programmers in Iraq. The findings show also that the Iraqi student teachers are aware of the importance of the mass media in developing their linguistic habits. The results obtained show that those learners are obviously exposed to a GA type of English through the mass media which serve as a vehicle of the American linguistic influence. This exposure to a natively spoken American English affects, to certain extent, the learners’ phoneme realizations and, consequently, word pronunciations.